2014
DOI: 10.7860/jcdr/2014/9139.4585
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dimensional Accuracy of Addition Silicone of Different Consistencies with Two Different Spacer Designs - In-vitro Study

Abstract: Introduction: Dimensional accuracy of impression materials is crucial for the production of working casts in Fixed Prosthodontics. The accurate replication of tooth preparations and their arch position requires impression materials that exhibit limited distortion. Methods:This study was conducted to comparatively evaluate the dimensional accuracy of additional silicones by comparing two different techniques and spacer designs, by measuring the linear changes in interpreparation distance. The impressions were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
6
1
1
Order By: Relevance
“…Two spacers were used for molding, one only covering the die and the other covering the die and the toothless gap. The authors concluded that the impression method, in which the spacer covered the die and the toothless gap simultaneously was more accurate [16]. The results of this study have not been consistent with ours.…”
Section: Discussioncontrasting
confidence: 84%
“…Two spacers were used for molding, one only covering the die and the other covering the die and the toothless gap. The authors concluded that the impression method, in which the spacer covered the die and the toothless gap simultaneously was more accurate [16]. The results of this study have not been consistent with ours.…”
Section: Discussioncontrasting
confidence: 84%
“…The silicone with evenly distributed layer covers the impression surface, penetrating into the undermined areas and adheres well to the tray after the polymerization. Most important is however the fact that in the evenly distributed layer with a moderate thickness the total value of the permanent deformations in the silicones is insignificant [31,34].…”
Section: Discussionmentioning
confidence: 99%
“…Most in vitro studies focusing on the accuracy of impressions used simplified master models with 1 to 3 truncated cone-shaped metal forms to simulate abutment teeth with full crown preparations. 18 19 20 24 25 26 27 28 29 Such idealistic and highly standardized settings facilitated a perfectly controlled space for the wash material. Their ability to reproduce the clinical situation were, however, limited due to missing undercuts and interproximal areas, and the documented accuracy was potentially overrated.…”
Section: Discussionmentioning
confidence: 99%